Osteopontin expression by CD103(−) dendritic cells drives intestinal inflammation - Kourepini, Evangelia (National Academy of Sciences, 2014)
Intestinal CD103(−) dendritic cells (DCs) are pathogenic for colitis. Unveiling molecular mechanisms that render these cells proinflammatory is important for the design of specific immunotherapies. In this report, we demonstrated that mesenteric lymph node CD103(−) DCs express, among other proinflammatory cytokines, high levels of osteopontin (Opn) during experimental colitis. Opn expression by CD103(−) DCs was crucial for their immune profile and pathogenicity, including induction of T helper (Th) 1 and Th17 cell responses. Adoptive transfer of Opn-deficient CD103(−) DCs resulted in attenuated colitis in comparison to transfer of WT CD103(−) DCs, whereas transgenic CD103(−) DCs that overexpress Opn were highly pathogenic in vivo. Neutralization of secreted Opn expressed exclusively by CD103(−) DCs restrained disease severity. Also, Opn deficiency resulted in milder disease, whereas systemic neutralization of secreted Opn was therapeutic. We determined a specific domain of the Opn protein responsible for its CD103(−) DC-mediated proinflammatory effect. We demonstrated that disrupting the interaction of this Opn domain with integrin α9, overexpressed on colitic CD103(−) DCs, suppressed the inflammatory potential of these cells in vitro and in vivo. These results add unique insight into the biology of CD103(−) DCs and their function during inflammatory bowel disease.